2022
DOI: 10.3201/eid2808.211567
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis variant natto Bacteremia of Gastrointestinal Origin, Japan

Abstract: B acillus subtilis is a gram-positive, rod-shaped, spore-forming bacterium temporarily present in the human gastrointestinal tract (1). The presence of B. subtilis in clinical specimens indicates contamination, but rare cases of bacteremia have been reported in Japan (2). Previous reports have attributed bacteremia in Japan to gastrointestinal origin but of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…natto and other species of B. subtilis rarely induce infection; however, there are several reports of infection by B. subtilis subsp. natto, such as bloodstream infections and meningitis in natto consumers 1–3,6 . To our knowledge, this case is the first report of community‐acquired pneumonia via this pathogen.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…natto and other species of B. subtilis rarely induce infection; however, there are several reports of infection by B. subtilis subsp. natto, such as bloodstream infections and meningitis in natto consumers 1–3,6 . To our knowledge, this case is the first report of community‐acquired pneumonia via this pathogen.…”
Section: Discussionmentioning
confidence: 75%
“…natto, such as bloodstream infections and meningitis in natto consumers. 1 , 2 , 3 , 6 To our knowledge, this case is the first report of community‐acquired pneumonia via this pathogen. The mechanism of pneumonia is unclear.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The other four described a potential safety concern. In the four papers there were problems related to the identification methodology used (Yeltekin et al, 2022, Fugaban et al, 2022, Tokana et al, 2022, Tanaka et al, 2022. The paper of Yeltekin et al ( 2022) reported a negative effect of B. subtilis infection on trout health but there was no clear link between the infectious agent and the trout affected, making the source attribution unclear.…”
Section: Bacillus Sppmentioning
confidence: 99%